Knowledge Construction Process in an Open Learning System Among Technical and Vocational Education and Training (TVET) Practitioners - Hashim, Suhaizal; Utami, Pipit; Abdul Rahman, Mohd Hishamuddin; Jumaat, Nurul Farhana; Eh Phon, & Danakorn Nincarean (Journal of Technical Education and Training, 2019)
Assessment is a method to determine the level of learning and the process of documenting knowledge, attitudes, skills and beliefs. Through this literacy assessment, instructor will have an opportunity to apply relevant strategies, principles, methods and procedures that are considered relevant during the learning and teaching process. However, most of us familiar with information and communication technology (ICT) based modes of delivery but less familiar with the needs and challenges face in Technical Vocational Education and Training (TVET) sector. Thus, this study was conducted to investigate whether the process of knowledge construction in an open learning system can assist TVET practitioners in performing tasks that needed to be completed as an important element in assessment in one of their class subject. Computer Supported Collaborative Learning (CSCL) is based on the pedagogical process of observation where these TVET practitioners will learn progressively through active group interaction. The study was conducted on 61 TVET practitioners and 2 instructors from two classes that were taught using an open learning system environment through Moodle in their learning and teaching process. This study used a quantitative design approach and supported by quantitative and qualitative data. The results of this study indicated that the process of knowledge construction in this open learning system has helped TVET practitioners to perform well in tasks that needed to be completed for their subject. The effort through this open learning system has also encouraged TVET practitioners to build a meaningful knowledge in a consistent method. The instructor need to encourage all TVET practitioners to complete the tasks in the form of problem solving methods, analyse, predict and encourage them to explore further to justify their answers.